Technical note on the introduction of partridge coloured Hungarian chicken in the mekong delta of Vietnam - Lan Phuong, Thieu Ngoc; Bódi, László; Dau, N. T.; Thuy Linh, N.; Thanh My, N.; Minh Thu, P. T.; Dong Xuan, K. D. T.; Szalay, István (Animal welfare, Ethology and Housing Systems (AWETH), 2016)
The paper aims to provide a brief agricultural profile of Tra Vinh province, informative adaptation results of Partridge coloured Hungarian chicken (PH) in Mekong Delta and describe the procedure to introduce PH into Tra Vinh province. During the introducing process, flexibility, consideration of the local condition (temperature, humidity, daily sunlight…), and availability of local resources such as bamboo blind, rice husk is essential for introducing a new chicken breed into Mekong Delta. For this, practical examples are given in the study. Regarding adaptation results, relatively high survival rate (89.6%) of PH was recorded at the end of 8th week. Although the recorded data of PH in Tra Vinh is limited, their performance is expected to be equally good or even better in comparison with that obtained in the sub-tropical climatic zone (North Vietnam). Further studies of PH adaptability in Mekong Delta for sustainable, traditional production and crossing purposes, as well as the involvement of chicken caravans to free range farming are recommended.